Heteroatom effect on photophysical properties of 2-(2′-hydroxyphenyl)benzimidazole and its derivatives as fluorescent dyes: A TD-DFT study - Natthaporn Manojai (2018)
© 2017 Elsevier B.V. The effects of hetero nitrogen substitution on the photophysical properties and excited-state intramolecular proton transfer (ESIPT) of HBX derivatives (HBI, HBO and HBT where X=NH, O and S, respectively) were investigated using density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations at B3LYP/6-311+G(d,p) level, which is the suitable method of choice validated from various density functionals. Geometries and absorption spectra of all derivatives as well as emission spectra of selected derivatives were calculated at the same level of theory. The hetero nitrogen substitution of HBX resulted in the red shift emission spectra, which implies that the lone pair of electron in the substituted nitrogen has the effect on the π-conjugated system. In addition, results of frontier molecular orbital analysis show that vertical S 0 →S 1 transition of these molecules corresponds essentially to the excitation from HOMO (π) to LUMO (π*). The potential energy curves (PECs) of selected derivatives were used to investigate the occurrence of ESIPT and the chance was found in this order: HBT > HBI > HBO. The hetero nitrogen substituted on 1,4 and 3,4 position of HBX derivatives could easily facilitate the ESIPT process, because the nitrogen substitution makes O–H bond of selected HBX derivatives weaker than those of other derivatives and the hydrogen bond in N–H becomes stronger in the excited state, resulting in lower PT barrier. The obtained information of the electronic structure, the photophysical property and the chance of ESIPT of hetero nitrogen substituted HBX molecules is useful for molecular design of fluorescent molecular probes.